Indications for gastrointestinal endoscopy in childhood. Issue 12 (31st May 2016) - Belsha, D; Bremner, R; Thomson, M
Abstract : Endoscopic examination of the gastrointestinal tract (GIT) for diagnostics and therapy in children has evolved markedly over the last 20 or so years and is now usually undertaken by paediatric endoscopists. Updated diagnostic and management guidelines for common disorders including coeliac disease, gastro-oesophageal reflux disease, eosinophilic oesophagitis and inflammatory bowel disease highlight the central role of endoscopy. Therapeutic endoscopic approaches are also now widely available and further broaden the referral spectrum to include treatment of GIT bleeding, gastrostomy insertion, dilation of strictures and polypectomy. Lastly, the advent of newer technologies allows the examination of hitherto inaccessible areas of the GIT such as the mid-small bowel by wireless capsule video-endoscopy and enteroscopy. We summarise recent current practice and clinical guidelines, focussing on the key indications for referrals that are likely to require endoscopic assessment.